THE EFFECTIVENESS OF ONLINE SERVICE AN INTELLIGENT LOOK-UP PROGRAM IN THE OCCUPATION AND CIVIC SERVICE OF TABALONG REGENCY - Norhalidah; Asmui; Rahma Yuliani (Jurnal PubBis, 2023)
This study aims to describe the effectiveness of the E-KTP service in the Smart Pelanduk program at the Tabalong Regency Population and Civil Registration Service and to identify the inhibiting factors for the E-KTP service in the Smart Pelanduk program at the Tabalong Regency Population and Civil Registration Service. This study uses a qualitative research method with a qualitative descriptive approach with three data collection techniques, namely interviews, observation and documentation. The key informants in this study were the intelligent slow down team, village officials, and the community who participated in the smart slow down program. The data that has been collected will be analyzed using the analysis interactive model from Miles and Huberman. The results of this study indicate that based on the E-KTP Service of the Smart Penetrating Program for the accuracy of program targets, the socialization of the program and program objectives is appropriate and runs smoothly in accordance with the objectives of the intelligent rattlesnake program. Monitoring is still lacking so that program constraints are in vulnerable places. It was not resolved in place at the time of the implementation of the Smart Pelanduk Breakdown. Therefore, there were several factors and in the Smart Pelanduk Breakdown service program, namely non-periodic service, not all printing could be carried out on the spot, the officer who broke the smart trigger was different, then there were several villages for poor internet access. adequate. The results of this study suggest 1) Evaluation needs to be carried out for the sustainability of the intelligent slowdown program so that it can be minimized and even there are no more errors in service. So that the service can continue to run better. 2) The need for monitoring because to provide assurance of certainty and quality control so that the implementation of the program is always in the rules and provisions of the program that has been set. Keywords: Effectiveness, Service, E-KTP, Breaking Down Smart Program